Impact of health information technology adoption and its drivers on quality of care & patient safety in the health care sector of Pakistan - Faiza Ijaz; Naveed Iqbal Chaudhry (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
This research aims to examine the impact of IT launch, technical support regarding IT, and the length of IT usage on healthcare outcomes including patient safety and quality of care. This study examines health information technology adoption as a mediator in this research model. To accomplish this purpose, the researchers collected data through a selfadministered questionnaire from people working in the health sector of Pakistan. Data was analyzed by using two statistical software SPSS and AMOS covering descriptive analysis, confirmatory factor analysis, and structural equation modeling. Results of the study impose that IT launch has a positive and significant impact on patient safety and quality of care. Length of IT usage also has a positive and significant impact on patient safety and quality of care. The technical support regarding IT has a positive and significant impact on patient safety but an insignificant impact on the quality of care. Moreover, results indicate that health IT adoption plays a significant mediating role in this research model.
Keywords: 330; health information technology adoption; patient safety; quality of care; technological factors; Information technology launch; technical support; length of usage oftechnology